2012
DOI: 10.1100/2012/361698
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the Antioxidant Capacity in Beverages Containing Tea Extracts during Storage

Abstract: The aim of this work was to determine antioxidant capacity of beverages containing black, white, and green tea extracts using the photochemiluminescence method, and to monitor its changes based on the storage temperature and time. Samples were stored at two different temperatures (refrigerated at 4°C and laboratory temperature 22°C), analyzed after opening of the original package, and consequently after 4 and 7 days. Results of the antioxidant capacity are expressed as the standard equivalents, that is, ascorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…On the other hand, Kopjar et al (2009) reported a loss of the 10.38% in the total phenols content and the 4.07% in the DPPH antioxidant capacity after one week of storage at room temperature in water-soluble green tea extract. Although Nekvapil et al (2012) used another method, they obtained findings similar to ours in the loss of the antioxidant capacity. They observed a decrease of 16% and 24% in the antioxidant capacity at four and seven days of storage at 22 °C, respectively, in a commercial green tea with aloe vera.…”
supporting
confidence: 79%
“…On the other hand, Kopjar et al (2009) reported a loss of the 10.38% in the total phenols content and the 4.07% in the DPPH antioxidant capacity after one week of storage at room temperature in water-soluble green tea extract. Although Nekvapil et al (2012) used another method, they obtained findings similar to ours in the loss of the antioxidant capacity. They observed a decrease of 16% and 24% in the antioxidant capacity at four and seven days of storage at 22 °C, respectively, in a commercial green tea with aloe vera.…”
supporting
confidence: 79%
“…Storage stability of green tea infusions depending on packaging material used (glass, PET, and retortable pouch) was evaluated by Kim et al (2011b). It was reported that cold storage at 4°C of tea beverages in PET bottles ensures a slower decrease in catechin content in white, black, and green teas (Nekvapil et al, 2012). The antioxidant capacity of green tea infusions decreased by 18, 14, and 30% in glass, PET, and retortable pouch, respectively, during the 12 weeks of storage.…”
Section: Storage Of Tea Leaves and Tea Beveragesmentioning
confidence: 99%
“…The percentage reductions are close to those observed for the antioxidant capacity (14 and 22%) measured by the ABTS method, which suggests that the reductions in TPC were accompanied by the same proportions of loss in the capture of the free radical ABTS displayed by ready-to-drink teas. Development, v. 9, n. 10, e219108160, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8160 11 No different behavior was observed on AC decay among formulations of teas added of fruit juices and the natural tea, contrary to the study of Nekvapil et al (2012) where the addition of fruit juices as lemon and peach implied in a positive impact on the antioxidant capacity of beverages containing white, black and green tea extracts.…”
Section: Antioxidant Capacity Abts For Green and Black Drinksmentioning
confidence: 94%
“…The authors suggest that differences were caused by different oxygen and light permeability of packaging materials. Nekvapil et al (2012) reported that cold storage at 4 °C of tea beverages in PET bottles ensures a slower decrease in antioxidant capacity in white, black, and green teas, compared to mild temperatures (22 °C).…”
Section: Antioxidant Capacity Abts For Green and Black Drinksmentioning
confidence: 99%